PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID APLIKASI PEMBELAJARAN BANGUN DATAR “SIPEMBADA” UNTUK SISWA KELAS IV SEKOLAH DASAR - Sutriyani Adinda Putri; Sukirwan Sukirwan; Trian Pamungkas Alamsyah (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
The researchers aim to develop Android-based interactive multimedia products in “Aplikasi Pembelajaran Bangun Datar (SIPEMBADA)”. SIPEMBADA android-based interactive multimedia product was developed using the smartapps creator software.The development method uses the Borg and Gall model in sugiyon. The development procedure used is 1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) revision design, (6) product trial, (7) product revision, (8) trial use, (9) final product revision. Data we collected through observation, interviews, documentation, and questionnaires. To determine the feasibility of the product, an assessment is carried out by experts. Media experts obtained a percentage value of 77.2% in the appropriate category, material experts obtained a percentage value of 86.5% in very appropriate category, and mathematics learning experts in elementary schools obtained a percentage score of 78.9% in the appropriate category, The results of product trials by students obtained a percentage value of 75.8% in the appropriate category, as well as the results of the trial use by students obtained a percentage value of 90.4% with a very appropriate category.